КРАТКИЕ ДАННЫЕ ПО БИОЛОГИИ И ЗАРАЖЕННОСТИ ГЕЛЬМИНТАМИ САЙГАКА (Saiga tatarica L., 1766) В КАЗАХСТАНЕ (Experimental biology, 2009)
Given astructure of types and report on some questions of ecology of helminthes, all three populations of saigaks in Kazakhistan
Keywords: helminthes